Process parameter interaction in microforming - Eichenhüller, Bernd; Engel, Ulf; Geißdörfer, Stefan (Proceedings of the 11th ESAFORM2008 conference on material forming, 2008)
Microforming processes, size effects and the influence of distinctive parameters on the forming process are been investigated for a long time. This paper presents some results of parameter interactions influencing the microforming process. The effects and interactions of five selected parameters are investigated for a full backward extrusion of small pins by means of a full factorial experimental design. The temperature-pin diameter interaction is used to give an example of an obvious and significant parameter interaction. © Springer/ESAFORM 2008.
LFT Import::2019-08-05 (326)
Keywords: Cu-ETP; Microforming; Parameter interaction; Size effects